The Effect of Work Motivation, Work Discipline and Job Satisfaction on Employee Performance - Esti Dwi Winanti; Sukaris Sukaris; Tri Ariprabowo; Alkusani Alkusani; Heru Baskoro; Indro Kirono (INNOVATION RESEARCH JOURNAL, 2023)
This study aims to examine the effect of motivation and work discipline and job satisfaction on performance. The number of samples in this study were 78 employees at PT. Bank Pengkreditan Rakyat Syariah Mandiri Gresik, using the technical method Probability Sampling type Simple Random Sampling. Collecting data in this study is using questionnaire and interviews. The data analysis technique used is multiple linear regression analysis. The results of this study concluded that the results of simultaneous testing of motivation, work discipline and job satisfaction have a significant effect on employee performance. Partial test results Motivation has a significant effect on employee performance, work discipline also has a significant effect on employee performance and job satisfaction has a significant effect on employee performance.